Diseases of wild strawberries in Primorye - O. A. Sobko; A. S. Didora; N. G. Boginskaya; N. V. Matsishina (Овощи России)
Relevance. Garden strawberry (Fragaria x ananassa Duch.) is one of the most popular and widespread berry crops in the world. One of the reasons for the strawberries low yields is the loss of production from fungal diseases. Especially harmful is pathogens complex affect. One of the fusariosis distinctive features is a specific etiology – the participation of a different types complex of the genus Fusarium fungi in the pathogenic process, which differ in biological properties and are adapted to certain environmental conditions. The pathogen of Botrytis cinerea gray rot parasitizes the culture year-round. Various forms of strawberry root rot caused by pathogens of the genus Phytophthora are poorly studied diseases. Oomycetes of the genus Phytophthora are sources of transient forms of apparently healthy plants withering, associated with the appearance of horns necrosis. These processes occurrence is primarily due to the high harmfulness of these pathogens, that can cause death from 40 to 78% of strawberry plants during the growing season. The object of this work was to establish the species composition of the garden strawberries diseases in the Primorsky Territory and to develop recommendations on measures to control them.Methods. The determination of pathogens was carried out by microscopy and passage of pure culture on differential media (Hella medium, carrot-sucrose agar) according to E. Blagoveshchenskaya (2015).Results. It has been established that in the Primorsky Territory, gray rot, late blight and fusariosis received the highest prevalence among diseases of under coverage strawberry. The causative agent of late blight was previously defined as Phythophtora cactorum (Lebert &. Cohn) Schröd, of the gray rot as Botrytis cinerea, of the fusariosis as Fusarium oxisporum Schlecht. ex Fr. f. sp. fragariae Winks et Williams. Gumat K, Agat-25K, Switch 62.5 WG, Teldor 50 WG are effective drugs to contain its harmfulness and spread. As a result of the measures taken, the spread of the disease decreased to 40%, productivity increased by 1.5 times.